THE EFFECT OF NOISE STUDY AT CITY PLANNING FOR SPECIFYING THE USES OF LAND - Ezzy, Nidaa (Anbar Journal of Engineering Sciences, 2008)
The research is interested in the noise sources that occur inside the cities. That the human being are subjected inside there homes, the way it maybe transfer and the way to treat this problem and control it by achieving a good planning to the city before the construction starts. The architecture role appears when planning the cities by defining the best way to use the land for and find the practical balance between the noise pollution the land suffer from. And also to indicate the locations of the housing area. in addition to locate the external and internal noise sources and put successful solutions to treat and control it by planning and design. A housing area at AL-SAQLAWIA a city near AL-ANBAR TECHNICAL INSTITUT was studied by distributing a (100) questionnaires for the people living at this area to recognize their opinion about the noise sources inside and outside their homes and how far it affect their life to find a table with conclusion about this object which contain a comparison between the house location near the street and far a way the street and transfer the results into graphs to explain the relation between the noise sources and the percentage ratio for the opinions of the living people.